A utilização de material didático impresso para o ensino de um modelo de classificação do esporte na educação física escolar - Barroso, André Luís Ruggiero [UNESP] (2015)
This study was related to the sport classification system, using internal logic as a reference, based on the criteria of cooperation, interaction with the opponent, comparative performance and tactical objectives of the action, using printed educational material - teacher's notebook and student's notebook. Thus, the aim of the study was to investigate which are the relevant changes that should be made by physical education teachers, working in the eighth and/or ninth grade regarding the educational material, to teach the sport classification system, developed by the Rio Grande do Sul Department of State Education, according to the existing teaching needs, and whether these changes address other groups of teachers who work at the same level of education. Using the action research method, this study had the effective participation of seven teachers, who were divided into two groups: A - developed the lessons with original educational material and B - used the teaching materials modified by the members of the first group. The results were organized into three categories for discussion: understanding and assessment of the sport classification system, understanding and assessment of educational material, implementation of the educational material related to the sport classification system. In the first category, favorable factors related to teaching of the classification system were observed, mainly emphasizing better presentation, organization and structuring of content and the diversity of the sports that were taught. Regarding the second category, initially the teachers showed insecurities and fears, mainly due to not having experience in dealing with the educational material, however, after using the material, they emphasized that it can be an important teaching tool, which helps the pedagogical process, as long as the teacher is allowed to make changes in accordance to their educational realities. As for the third category, a big part of...